Mortality Attributable to Ambient Air Pollution: A Review of Global Estimates. (9th January 2023) - Pozzer, A.; Anenberg, S. C.; Dey, S.; Haines, A.; Lelieveld, J.; Chowdhury, S.
Abstract: Since the publication of the first epidemiological study to establish the connection between long‐term exposure to atmospheric pollution and effects on human health, major efforts have been dedicated to estimate the attributable mortality burden, especially in the context of the Global Burden of Disease (GBD). In this work, we review the estimates of excess mortality attributable to outdoor air pollution at the global scale, by comparing studies available in the literature. We find large differences between the estimates, which are related to the exposure response functions as well as the number of health outcomes included in the calculations, aspects where further improvements are necessary. Furthermore, we show that despite the considerable advancements in our understanding of health impacts of air pollution and the consequent improvement in the accuracy of the global estimates, their precision has not increased in the last decades. We offer recommendations for future measurements and research directions, which will help to improve our understanding and quantification of air pollution‐health relationships. Plain Language Summary: In this work we review the estimates of excess mortality attributable to outdoor air pollution at the global scale, by comparing studies available in the literature. We find large differences between the estimates, mainly caused by mathematical function used to describe the pollution‐health link, as well as the number of health outcomes included in the calculations. We showed that, despite the considerable advancements in our understanding of health impacts of air pollution, the precision of the estimates has not increased in the last decades. We offer recommendations for future measurements and research directions, which will help to improve our understanding and quantification of air pollution‐health relationships. Key Points: Large differences are present in the published estimates of excess mortality attributable to outdoor air pollution at the global scale The differences are mostly due to the exposure response functions as well as the number of health outcomes included in the calculations Although the accuracy of the global estimates has improved, their precision has not increased in the last decades